2022
DOI: 10.3390/brainsci12060804
|View full text |Cite
|
Sign up to set email alerts
|

No Sex Differences in Self-Reported Childhood Maltreatment in Major Depressive and Bipolar Disorders: A Retrospective Study

Abstract: Background: We investigated, for the first time, whether there are any sex differences in retrospective self-reported childhood maltreatment (CM) in Italian adult patients with major depressive disorder (MDD) or bipolar disorder (BD). Furthermore, the potential impacts of patients’ age on the CM self-report were investigated. Methods: This retrospective study used the data documented in the electronic medical records of patients who were hospitalized for a 4-week psychiatric rehabilitation program. CM was asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The term Adverse Childhood Experiences (ACEs) has also been used to describe a wide range of traumatic or stressful experiences during childhood and adolescence. Children and adolescents who experienced maltreatment and other Adverse Childhood Experiences (ACEs) are at increased risk for developing borderline personality disorder symptoms [ 92 ], major depressive disorder or bipolar disorder [ 93 , 94 ]. Moreover, ACEs have been demonstrated as a predictor of worse outcomes during anti-depressant treatments, although a recent systematic review did not report a difference in treatment response among depressive patients with or without a history of childhood maltreatment [ 94 ].…”
Section: Adverse Childhood Experiences (Aces) and Psychopathology In ...mentioning
confidence: 99%
“…The term Adverse Childhood Experiences (ACEs) has also been used to describe a wide range of traumatic or stressful experiences during childhood and adolescence. Children and adolescents who experienced maltreatment and other Adverse Childhood Experiences (ACEs) are at increased risk for developing borderline personality disorder symptoms [ 92 ], major depressive disorder or bipolar disorder [ 93 , 94 ]. Moreover, ACEs have been demonstrated as a predictor of worse outcomes during anti-depressant treatments, although a recent systematic review did not report a difference in treatment response among depressive patients with or without a history of childhood maltreatment [ 94 ].…”
Section: Adverse Childhood Experiences (Aces) and Psychopathology In ...mentioning
confidence: 99%
“… 23 , 24 However, the question of whether there are sex differences in self-reported CM among different populations remains inconclusive. For instance, a study by Caldirola et al 25 explored sex differences in retrospective self-reported CM in Italian adult patients with major depressive disorder or bipolar disorder, revealing that both women and men with MDD or BD experienced a similar and considerable burden of CM. Similarly, research conducted by Liu et al 26 investigated sex differences in the complex interconnections among various types of CM, post-traumatic stress disorder, and depression, identifying notable sex discrepancies in the relationship between different forms of maltreatment and psychopathological symptoms.…”
Section: Introductionmentioning
confidence: 99%